(untitled) (Orinoquia, 2025)
Fertilizers are materials, both natural and manufactured, that supply essential nutrients for the proper development of plants, thereby improving production, yield, and the quality of crops and food. In the context of organic agriculture, the use of natural and sustainable sources for fertilizer formulation represents a key strategy to reduce environmental impact and dependence on chemical inputs. The objective of this study was to develop a semi-solid fertilizer from agro-industrial residues, contributing to the valorization of organic waste through an artisanal approach accessible to farmers. For this purpose, various residual materials were collected in the city of Cartagena, Colombia, including eggshells, banana peels, plantain peels, and coffee grounds. Calcium carbonate was extracted from the eggshells as a source of bioavailable calcium. Physicochemical analyses were conducted to characterize these residues and determine their viability as nutritional inputs. Subsequently, the semi solid fertilizer was formulated and its efficacy was evaluated by applying a 5 mL dose per plant, monitoring the growth of Tradescantia pallida over a 49-day period. The fertilizer exhibited relevant concentrations of essential minerals such as nitrogen (0.53%), magnesium (0.88%), calcium (6.14%), and phosphorus (1.04%). The results showed a positive response in plant growth and development, demonstrating the effectiveness of the product. The applied dose and frequency were sufficient to promote vegetative development, although further research is needed to evaluate multiple doses and morphological variables using more robust experimental designs. In conclusion, the developed formulation represents an effective alternative within the framework of organic agriculture, by utilizing locally available agro-industrial residues, reducing dependence on synthetic chemical products, and supporting a sustainable, regenerative, and economically accessible production model for small-scale farmers.